The Effect of Hypnobirthing on Maternal Anxiety Levels and Length of Labor in Independent Practicing Midwives in the Panyabungan Area, Mandailing Natal Regency - Khoiriyani, Kiki; Harahap, Seri Wahyuni; Rezeki, Sri; Lubis, Ayu Ulfah Nur (International Journal of Public Health Excellence (IJPHE), 2024)
The birth process is a natural event of conception in the form of a baby and placenta from the uterus which can cause anxiety. Anxiety in pregnant women, if not managed properly, will have an impact on the physical and psychological health of the mother and baby. This research uses a descriptive method. The research will take place in December 2021–May 2022 at PMB Lutfiana. A total of 40 mothers in active phase I labor were obtained using total sampling techniques. The data collection technique uses the STAI scale. Data analysis uses descriptive analysis. The age characteristics of respondents aged 20–35 years included 34 respondents (85%). The majority of elementary-middle school students with low education amounted to 21 respondents (52.5%). The majority of respondents did not work, 27 respondents (67.5%), and the majority of multiparous respondents, 31 respondents (77.5%). The majority of maternal anxiety during the active phase was at the severe anxiety level, namely 28 respondents (70%). The average anxiety score was 46.43, with a 95% CI of 43.01-49.84. The majority of mothers' anxiety levels in the active phase of labor are severe anxiety levels.